The Mystical and Scientific Significance of Rudraksha Beads: Exploring Their Role in Spiritual and Holistic Well-Being (SMC Journal Shadananda Multiple Campus, 2025)
Rudraksha beads, sacred in Hindu and Buddhist traditions, are revered for their role in meditation, prayer, and well-being. Derived from the Sanskrit words “Rudra” (Lord Shiva) and “Aksha” (tears), they hold deep spiritual symbolism, serving as a bridge between the physical and metaphysical. The study explores their mystical properties, such as mental peace, concentration, and protection against negative energies. From a scientific perspective, Rudraksha beads exhibit bio-electromagnetic properties, potentially influencing the human bio-field and offering therapeutic benefits. Research suggests they may contribute to stress reduction, heart rate variability, and overall health by aligning with the body's energy field. Additionally, their psycho-physiological effects include stress relief, mood regulation, and holistic well-being. Rudraksha beads remain relevant in modern wellness practices, blending ancient wisdom with contemporary healing systems. This study provides a balanced perspective, integrating both mystical and scientific viewpoints, emphasizing Rudraksha's enduring significance in spiritual, emotional, and physical wellness. It also underscores the need for further scientific exploration to better understand how these beads influence human well-being, reinforcing their status as timeless symbols of holistic health.